The Effectiveness of Using Flashcards in Teaching English Vocabulary to Vietnamese Young Learners: An Experimental Study at a Language Center in Binh Duong - Nguyen, Thanh Thai; Pham, Hong Thi Thanh (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Vocabulary is a crucial component of learning English. Among the various methods employed by teachers, using flashcards is one of the most commonly practiced approaches. But how effective is it? This study aims to evaluate the effectiveness of using flashcards in teaching vocabulary to Vietnamese young learners and to examine potential differences in learning outcomes between male and female students. The research was conducted at a language center in Binh Duong, involving 30 first-grade students aged 5 to 6, all of whom were beginner-level English learners. An experimental research design was implemented, with participants divided into two groups: a control group and an experimental group, each comprising 15 students. The experimental group was taught English vocabulary using flashcards, while the control group received instruction through traditional teaching methods without additional teaching aids. Data were collected through three assessments: a pre-test, a midterm test, and a post-test. The results demonstrated that flashcards are an effective tool for teaching English vocabulary to first-grade students. Additionally, the post-test revealed a significant difference in vocabulary acquisition between male and female students, with females outperforming their male counterparts when learning with flashcards. In conclusion, this study highlights the effectiveness of incorporating flashcards into vocabulary teaching and recommends their integration to improve learning outcomes. It also suggests tailoring teaching strategies to optimize vocabulary acquisition for both genders.